Sonochemical synthesis of MMoO4 (M = Ca, Sr and Ba) nanocrystals - Titipun Thongtem (2018)
MMoO4 (M = Ca, Sr and Ba) were successfully produced using M(NO3)2·2H2O and Na2MoO 4·2H2O in ethylene glycol by a 5 h sonochemical process. A tetragonal crystal system with a scheelite structure was detected using an X-ray diffractometer (XRD) and a selected area electron diffraction (SAED) technique. The calculated lattice parameters (a nm, c nm) are (0.5232, 1.1430), (0.5402, 1.2027) and (0.5560, 1.2766) for M = Ca, Sr and Ba, respectively. They are in accord with those of the corresponding JCPDS software. A transmission electron microscope (TEM) revealed the presence of nanocrystals in the products. Their sizes were 11.5 ± 3.1 nm, 15.9 ± 4.8 nm and 18.1 ± 4.8 nm for M = Ca, Sr and Ba, respectively. Their cristallographic planes were aligned in systematic arrays characterized using a high resolution transmission electron microscope (HRTEM). Six different vibration wavenumbers were detected using a Raman spectrometer and are specified as V1(Ag), v3(Bg), v 3(Eg), v4(Bg), v2(Ag) and vf.r.(Ag). A Fourier transform infrared (FTIR) spectrometer provided evidence of the scheelite structure with a Mo-O stretching vibration in MoO42- tetrahedrons at 740-950 cm -1.